2021
DOI: 10.5194/acp-21-9669-2021
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the anthropogenic reversal of the natural ozone gradient between northern and southern midlatitudes

Abstract: Abstract. Our quantitative understanding of natural tropospheric ozone concentrations is limited by the paucity of reliable measurements before the 1980s. We utilize the existing measurements to compare the long-term ozone changes that occurred within the marine boundary layer at northern and southern midlatitudes. Since 1950 ozone concentrations have increased by a factor of 2.1 ± 0.2 in the Northern Hemisphere (NH) and are presently larger than in the Southern Hemisphere (SH), where only a much smaller incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previous studies focused on O 3 –NO x -VOC sensitivity and found the O 3 increase was caused by the changes in precursor concentrations. , The increasing O 3 pollution is also partly attributed to the change in meteorological conditions, the increasing global background O 3 , , and the reduction of aerosol loadings. , Aerosols have a dual effect on tropospheric O 3 production. First, the aerosols could attenuate solar radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies focused on O 3 –NO x -VOC sensitivity and found the O 3 increase was caused by the changes in precursor concentrations. , The increasing O 3 pollution is also partly attributed to the change in meteorological conditions, the increasing global background O 3 , , and the reduction of aerosol loadings. , Aerosols have a dual effect on tropospheric O 3 production. First, the aerosols could attenuate solar radiation.…”
Section: Introductionmentioning
confidence: 99%
“…To improve air quality in China, strict clean air action was implemented in 2013 leading to substantial particulate matter pollution reduction in most Chinese cities. , Despite the successful reduction of primary pollutants, the increasing trend of O 3 was found in many Chinese cities. Thus, O 3 pollution has been gaining increasing attention in China. The aggravating O 3 pollution is also observed in the North Hemisphere due to the increasing anthropogenic emissions . Wildfire, , biomass burning, , and volatile chemical products (VCPs) add more obstacles to the O 3 mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…This cross-over is consistent with recent discussion of preindustrial ozone concentrations being larger in the southern hemisphere, which is dominated by oceans, than in the northern hemisphere, which has much larger continental areas. 32…”
Section: Resultsmentioning
confidence: 99%
“…This cross-over is consistent with recent discussion of preindustrial ozone concentrations being larger in the southern hemisphere, which is dominated by oceans, than in the northern hemisphere, which has much larger continental areas. 32 STE contribution to tropospheric burden: The relative contributions of the stratosphere and the continental photochemical production (P B,c ) to the tropospheric ozone burden can be evaluated within this model, since it places all non-linear aspects of the ozone budget into the determination of the first order loss terms in the BL compartments; the model then consists of a system of linear equations. As such, the contribution of each source to the burden of ozone in each compartment is mathematically separable.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Many studies show that the magnitude of the tropospheric O 3 burden and surface O 3 concentrations in remote areas can be simulated relatively well (Young et al, 2018;Griffiths et al, 2021). However, large differences still exist in simulated surface O 3 concentrations in highemission areas (Turnock et al, 2020), and there are large uncertainties in temporal trends (Tarasick et al, 2019) that cannot be captured well by global chemistry-climate models (Parrish et al, 2021). In addition, structural biases in O 3 caused by coarse model resolution are hard to eliminate and typically lead to higher surface O 3 concentrations in polluted areas (Wild and Prather, 2006;Stock et al, 2014).…”
Section: Introductionmentioning
confidence: 99%